'I have enjoyed teaching science more': changing the attitudes of primary teachers and pupils towards science. Issue 3 (2nd September 2022) - White, Elizabeth; Dickerson, Claire; Mackintosh, Julia
ABSTRACT: This article explores issues with primary science, changing attitudes towards primary science and the interrelationship between attitudes and experiences. It examines findings from research that investigated the views and experiences of twelve science leaders undertaking a professional development programme designed to develop primary science pedagogy and leadership. Qualitative data collected using questionnaires, an interview, focus group, and programme submissions were analysed thematically and using keywords. The findings suggest changes in science leaders' and teachers' attitudes towards teaching science and of pupils towards learning science. By considering attitudinal change as a particular form of learning leading to the acquisition of 'personal knowledge' after Eraut, this article raises questions about individual and social construction of attitudinal knowledge. It also explores the way attitudes and experiences interrelate and how teachers' professional development might influence collective attitudinal knowledge across school communities and, in turn, enhance individual learning.